Hubungan Antara Status Sosial Ekonomi Dengan Pemilihan Pelayanan Kesehatan Di Desa Karanggeneng Kecamatan Boyolali Kabupaten Boyolali Tahun 2016 - Ilhamdani, Anan Lamus; , Supratman, M.Kep, Ph.D; , Dian Nur Wulanningrum, S.Kp., Ns., M.Kep (2017)
A healthy body desired by every human in order to carry out various activities of life, in improving public health point of government need to extend public health care. Economic problems need attention, so people get health services like what they want. The aim of research to determine the relationship between socioeconomic status with sellection of health services in the Karanggeneng village of District Boyolali at 2016. This quantitative research with analytic survey, and cross sectional approach. The research population are 1288 head of the family in the Karanggeneng village of District Boyolali. Research sample are 360 respondents was obtained by simple random sampling technique. Collecting data using questionnaires, data analysis using non-parametric Spearman Rank test. The research result from non-parametric Spearman Rank test showed that the factors of education level, occupation, and income income had a p value = 0.001 with correlation coefficients (r), respectively 0.601; 0.676; and 0.479. Conclusion there is a relationship between socio-economic status of the factor of education level, occupation, and income level with sellection of health services in the Karanggeneng village of District Boyolali at 2016.